Taxation of Financial Intermediation : Theory and Practice for Emerging Economines - Honohan, Patrick (Washington, DC: World Bank and Oxford University Press, 2013)
This volume examines the possibilities and pitfalls to successful financial sector tax reform from theoretical, empirical and practical perspectives. It explores the possibilities and limitations of "big ideas" such as removal of all capital income taxation, the application of VAT to financial services or heavy reliance on financial transactions taxes. The risks of attempting to use financial sector taxes as corrective instruments are stressed. Two defensive criteria are advanced as key: making the financial tax system as arbitrage- and inflation-proof as is practicable. Each commissioned essay develops a distinct aspect of the area. Theoretical chapters model the impact of taxes on intermediaries, the design of optimal tax schemes, the role of imperfect information and the relationship with saving. Current practice in the industrial world and case studies of distorted national systems provide an empirical underpinning. Finally, experience with several of the main practical issues is discussed in chapters ranging from the income tax treatment of intermediary loan-loss reserves, the VAT, financial transactions taxes, deposit insurance and inflation. Contributors are distinguished academics and practitioners.